Giant cell tumour of tendon sheath masquerading as trigger finger. - N., Rahimawati; Syed Waseem Ahmad, Sharifah Roohi; Naicker, A. S.; Othman, Zanariah (Malaysian Orthopaedic Association, 2010)
We report a case of a 59-year-old female who presented in the general orthopaedic clinic with triggering of her right middle finger. She did not respond to conventional treatment methods; subsequently she underwent surgical open release under local anaesthesia. Five months postoperatively, the patient presented with signs and symptoms of acute flexor tenosynovitis, and was thought to have a postoperative infection. Re-examination by a hand surgeon raised the possibility of a different aetiology. Based on clinical findings and response to initial treatment, giant cell tumour of the flexor tendon sheath was suspected and later confirmed following surgical biopsy. A high index of suspicion and knowledge of the variegated presentations of giant cell tumour in the hand are beneficial in these types of cases.